2020
DOI: 10.3390/foods9010087
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Drying of Plant-Based Foods

Abstract: Vacuum freeze-drying of biological materials is one of the best methods of water removal, with final products of highest quality. The solid state of water during freeze-drying protects the primary structure and the shape of the products with minimal volume reduction. In addition, the lower temperatures in the process allow maximal nutrient and bioactive compound retention. This technique has been successfully applied to diverse biological materials, such as meats, coffee, juices, dairy products, cells, and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(139 citation statements)
references
References 130 publications
2
103
0
3
Order By: Relevance
“…Compared with other drying methods in terms of maintaining the final product quality, the lyophilization method is recommended as the best choice for drying fruits and vegetables. Because the absence of liquid water, lack of oxygen under vacuum and low temperatures, most of the deterioration reactions slow down or are practically stopped, aroma losses are minimized (Bhatta, Stevanovic Janezic, & Ratti, 2020). In previous studies, it has been reported that the lyophilization technique has significantly benefited in preserving phenolic compounds, color pigments (anthocyanins, carotenoids, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other drying methods in terms of maintaining the final product quality, the lyophilization method is recommended as the best choice for drying fruits and vegetables. Because the absence of liquid water, lack of oxygen under vacuum and low temperatures, most of the deterioration reactions slow down or are practically stopped, aroma losses are minimized (Bhatta, Stevanovic Janezic, & Ratti, 2020). In previous studies, it has been reported that the lyophilization technique has significantly benefited in preserving phenolic compounds, color pigments (anthocyanins, carotenoids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it has been reported that the lyophilization technique has significantly benefited in preserving phenolic compounds, color pigments (anthocyanins, carotenoids, etc. ), ascorbic acid, aroma components, and textural properties in fruits and vegetables (Bhatta et al., 2020; Gümüşay, Borazan, Ercal, & Demirkol, 2015; Palacios, Guillamón, García‐Lafuente, & Villares, 2014; Rajkumar et al., 2017; Rodrigues, Dos Santos, Bergamasco, & Madrona, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As the outer layer is covered by epicuticular waxex, freezedrying of whole shoots could contribute to build-up of internal pressure and lead up to material damage, making it more susceptible to external conditions (Bhatta et al, 2020). Therefore, it can be expected that raw material type also has a decisive impact on the stability of pigments during drying with different methods.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, a number of reviews have been conducted on the subject freeze-drying. However, most of these reviews have centered on the quality characteristics of the food product and improving the freeze-drying process with limited emphasis on the effect of the drying process on the grinding characteristics of the food [20][21][22] Therefore, the primary objective of this review was to provide an overview of the effect of freeze-drying on the quality attributes of agricultural products and to state the influence of freeze-drying on the grinding process. A review of the mathematical models for freeze-drying will also be provided.…”
Section: Introductionmentioning
confidence: 99%